IMPLEMENTASI PENDIDIKAN ISLAM YANG HUMANIS PADA MASA KEPEMIMPINAN KHULAFAUR RASYIDIN - Hawary, M. Shofiyyur Rahman; Gunawan, Hendra; Apip, M.; Banjarnaor, Riadi; Rifaldi, Muhammad; Darimus, Darimus (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This article aims to explore the concept of non-violent Islamic education based on the practices and principles implemented by the Khulafaur Rasyidin, namely Abu Bakar Ash-Shiddiq, Umar ibn Khattab, Utsman ibn Affan, and Ali ibn Abi Thalib. This study employs a qualitative approach using library research and historical-critical analysis of classical and contemporary literature. The findings reveal that the Khulafur Rasyidin prioritized educational principles grounded in compassion, dialogue, exemplary conduct, and community empowerment, while firmly rejecting physical and verbal violence in educational practices. Each caliph demonstrated a unique yet consistent approach rooted in humanistic and just Islamic values. The study concludes that the non-violent educational model exemplified by the Khulafaur Rasyidin is highly relevant for addressing modern educational challenges, particularly in developing a character-based and dignified learning system.